2013
DOI: 10.1007/s12265-013-9489-5
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-Induced Upregulation of Connective Tissue Growth Factor in Rabbit Cardiomyocytes

Abstract: Connective Tissue Growth Factor (CTGF, CCN2) is considered to play an important role in cardiac remodelling. We studied whether stretch is a primary stimulus to induce CTGF expression in vivo in rabbit heart, and in vitro in isolated cardiomyocytes and fibroblasts. Twenty weeks of combined volume and pressure overload resulted in eccentric left ventricular (LV) hypertrophy, with increased LV internal diameter (+36 %) and LV weight (+53 %). Myocardial CTGF mRNA and protein levels were substantially increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…By contrast, SRF and NFATc4 (both known target genes of miR‐133a) did not show any relation with miR‐133a in this study and are most likely not involved in the hypertrophic response in our model of local hypertrophy. In vitro studies showed that increased CTGF expression in isolated, stretched cardiomyocytes coincided with development of a hypertrophic response 1, 3. Moreover, in a rabbit model of eccentric hypertrophy, where strains and workload are expected to be high throughout the LV wall, CTGF was also found to be overexpressed 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, SRF and NFATc4 (both known target genes of miR‐133a) did not show any relation with miR‐133a in this study and are most likely not involved in the hypertrophic response in our model of local hypertrophy. In vitro studies showed that increased CTGF expression in isolated, stretched cardiomyocytes coincided with development of a hypertrophic response 1, 3. Moreover, in a rabbit model of eccentric hypertrophy, where strains and workload are expected to be high throughout the LV wall, CTGF was also found to be overexpressed 3.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed that increased CTGF expression in isolated, stretched cardiomyocytes coincided with development of a hypertrophic response 1, 3. Moreover, in a rabbit model of eccentric hypertrophy, where strains and workload are expected to be high throughout the LV wall, CTGF was also found to be overexpressed 3. Of note is that recent studies question the importance of CTGF in cardiac structural remodelling, indicating that while it is an important biomarker of myocardial remodelling, it most likely does not play a decisive role in this process24, 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Daily Trial, an association was found between change in predialysis SBP over the 12-month study period and change in LVM (slope estimate 6.6 g per 10 mm Hg in the group receiving 3/week HD and 10.1 g per 10 mm Hg in the group assigned to frequent HD) [17] . In the Daily Trial, a reduction in ECF or TIFL could affect LVM indirectly, via a reduction in blood pressure [26] , or volume overload reduction per se might effect a reduction in LVM, since fluid overload during the interdialytic period increases cardiac strain [1][2][3] and subsequently connective tissue growth [27] .…”
Section: Sbp and Reduction Of Extracellular Volume Expansionmentioning
confidence: 99%
“…The cyclophilin A gene was utilized as a reference to normalize the reactions (Blaauw et al 2013), and the cDNA from the control group was used as a calibrator for the assays. The relative expression of the calibrators was assigned a value of 1 unit.…”
Section: Relative Quantification By Real-time Pcrmentioning
confidence: 99%